Sebuah catatan tragedi 1965 : dari Pulau Buru sampai ke Mekah - Suparman, H. (Ujungberung, Bandung : Nuansa, 2006)
Autobiography of a former political prisoner of the Soeharto government, for alleged involvement with the Indonesian Communist Party
Includes index
Keywords: Suparman, H; Politicians -- Indonesia -- Biography; Political prisoners -- Indonesia -- Buru Island (Maluku) -- Biography; Indonesia -- Politics and government